Association of Lymphocyte-to-Monocyte Ratio With Survival in Advanced Gastric Cancer Patients Treated With Immune Checkpoint Inhibitor - Chen, Yang; Zhang, Cheng; Peng, Zhi; Qi, Changsong; Gong, Jifang; Zhang, Xiaotian; Li, Jian; Shen, Lin (Frontiers in Oncology, 2021)
Abstract Background Optimal prognostic biomarkers for patients with gastric cancer who received immune checkpoint inhibitor (ICI) are lacking. Inflammatory markers including lymphocyte-to-monocyte ratio (LMR), platelet-to-lymphocyte ratio (PLR), and systemic inflammation index (SII) are easily available. However, its correlation with ICI is unknown in gastric cancer. Here, we evaluated the potential association between LMR, PLR, and SII with clinical outcomes in gastric cancer patients undergoing ICI therapy. Methods We examined LMR, PLR, SII at baseline and 6 (±2) weeks later in 139 patients received ICI therapy between August 2015 and April 2019 at Peking University Cancer Hospital (Beijing, China). Landmark analysis at 6 weeks was conducted to explore the prognostic value of LMR, PLR, and SII on progress-free survival (PFS), and overall survival (OS). A Cox proportional hazards model was used to compute mortality hazard ratios (HRs) for LMR, adjusting for potential confounders including age, sex, ECOG, tumor location, tumor differentiation, tumor stage, line of therapy, and type of anti-PD-1/PD-L1 therapy. Results Among 139 patients, 103 (74.1%) were male, median age was 60 years. Median duration of therapy was 6 cycles. We observed that both LMR at baseline and week-6 were independent prognostic factors. Patients with a higher LMR (≥ 3.5) at baseline or week-6 had superior PFS [baseline: HR 0.58, 95% confidence interval (CI): 0.38-0.91; week-6: HR 0.48, 95%CI: 0.29-0.78] and OS (baseline: HR 0.38, 95%CI: 0.24-0.62; week-6: HR 0.52, 95%CI: 0.31-0.88) compared with patients with a lower LMR (< 3.5). Furthermore, for patients with both LMR ≥ 3.5 at baseline and LMR ≥ 3.5 at week-6 were estimated to have much better PFS (HR 0.41, 95% CI: 0.23-0.72) and OS (HR 0.34, 95%CI: 0.18-0.64) than patients with both LMR < 3.5 at baseline and LMR < 3.5 at week-6. Conclusions Baseline and early changes in LMR were strongly associated with survival in gastric cancer patients who received ICI therapy, and may serve to identify patients most likely to benefit from ICI.